2021
DOI: 10.3390/pharmaceutics13030398
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord, Maternal Milk, and Breastfed Infant Levetiracetam Concentrations Monitoring at Delivery and during Early Postpartum Period

Abstract: (1) To obtain objective information about levetiracetam transplacental passage and its transport into colostrum, mature milk, and breastfed infants, we analyzed data from women treated for epilepsy between October 2006 and January 2021; (2) in this cohort study, maternal, umbilical cord, milk, and infant serum concentrations were measured at delivery, 2–4 days postpartum (colostrum) and 7–31 days postpartum (mature milk). Paired umbilical cord serum, maternal serum, breastfed infant serum, and milk concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The paired milk/maternal serum concentration ratio of VPA was found to be much lower than the infant/maternal serum concentration ratio, which is supported by comparing the distribution of these two ratios in Figure 2, in which the infant/maternal serum concentration ratio shifted to higher values (i.e., "to the right"). This result was diametrically different from levetiracetam and topiramate, in which we observed that the mean milk/maternal serum concentration ratio was markedly higher than the mean infant/maternal serum concentration ratio, and that a movement of the infant/maternal serum concentration ratio to lower values (i.e., "to the left") was apparent [35,36]. Paired colostrum and mature milk concentrations of VPA were measured on or under the lower limit of quantification, respectively, and were not significantly different between these two time periods.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The paired milk/maternal serum concentration ratio of VPA was found to be much lower than the infant/maternal serum concentration ratio, which is supported by comparing the distribution of these two ratios in Figure 2, in which the infant/maternal serum concentration ratio shifted to higher values (i.e., "to the right"). This result was diametrically different from levetiracetam and topiramate, in which we observed that the mean milk/maternal serum concentration ratio was markedly higher than the mean infant/maternal serum concentration ratio, and that a movement of the infant/maternal serum concentration ratio to lower values (i.e., "to the left") was apparent [35,36]. Paired colostrum and mature milk concentrations of VPA were measured on or under the lower limit of quantification, respectively, and were not significantly different between these two time periods.…”
Section: Discussioncontrasting
confidence: 81%
“…This result corresponds to Figure 3, which presents an almost continuous decrease in VPA-breastfed infant serum concentrations at three time points (delivery-colostrum-mature milk). Different declines in breastfed infant serum concentrations were observed for levetiracetam, in which a rapid decrease in concentrations was found between the delivery and colostrum periods and thereafter the concentrations were stable [35].…”
Section: Discussionmentioning
confidence: 95%
“…Available information on maternal serum and milk concentrations as well as on serum concentrations in breastfed infants is extensive. Based on 82 published cases, the levetiracetam milk/maternal serum concentration ratios have ranged from 0.58 to 1.79, with averages in most studies in the order of 1.0 [27, 42-45]. Infant/maternal serum concentration ratios were reported in 121 mother‐child pairs, and ranged from below the level of quantification in infant serum to a ratio of 0.71, with a reported average in individual studies in most cases at around 0.1 [14, 27, 42-45].…”
Section: Resultsmentioning
confidence: 99%
“…Available information on maternal serum and milk concentrations as well as on serum concentrations in breastfed infants is extensive. Based on 82 published cases, the levetiracetam milk/maternal serum concentration ratios have ranged from 0.58 to 1.79, with averages in most studies in the order of 1.0 [27,[42][43][44][45].…”
Section: Levetiracetammentioning
confidence: 99%
See 1 more Smart Citation